2002
DOI: 10.1016/s0002-9440(10)64887-0
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of the Matrix Metalloproteinases MMP-2, MMP-9, and MT1-MMP as Membrane Vesicle-Associated Components by Endothelial Cells

Abstract: Production of matrix-degrading proteases, particularly matrix metalloproteinases (MMPs), by endothelial cells is a critical event during angiogenesis, the process of vessel neoformation that occurs in normal and pathological conditions. MMPs are known to be highly regulated at the level of synthesis and activation, however, little is known about the regulation of MMP secretion by endothelial cells. We found that cultured human umbilical vein endothelial cells shed vesicles (300 to 600 nm) originating from loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
381
3
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(409 citation statements)
references
References 30 publications
(40 reference statements)
19
381
3
3
Order By: Relevance
“…A discrepancy was found in the low MMP-2 transcript measured 3 and 5 days after bleomycin treatment and the high protein concentration of MMP-2 detected at the protein level. It has been reported that bleomycin can induce MMP-2 expression in alveolar epithelial cells (19,20), and some shedded MMP-2 was stored in endosomal vesicles for recycling (21). Thus, it is possible that we detected not only newly produced MMP-2 but also endosomestored MMP-2 at the protein level.…”
Section: Tnfrp55-mediated Signaling In Pathogenesis Of Sclerodermamentioning
confidence: 85%
“…A discrepancy was found in the low MMP-2 transcript measured 3 and 5 days after bleomycin treatment and the high protein concentration of MMP-2 detected at the protein level. It has been reported that bleomycin can induce MMP-2 expression in alveolar epithelial cells (19,20), and some shedded MMP-2 was stored in endosomal vesicles for recycling (21). Thus, it is possible that we detected not only newly produced MMP-2 but also endosomestored MMP-2 at the protein level.…”
Section: Tnfrp55-mediated Signaling In Pathogenesis Of Sclerodermamentioning
confidence: 85%
“…Both TIMP-2 and -4 have been shown to suppress EC tube formation in fibrin gels 51 and EC invasion through Matrigel was inhibited by TIMP-1 and -2. 56 In addition to this, TIMP-1, -2 and -3 have all been shown to inhibit EC migration and invasion in type I collagen gel assays. 52,57 The repeated observations of a correlation between MMP inhibition and reduced tumor angiogenesis provide strong evidence for the involvement of the MMPs in this process.…”
Section: Endogenous Inhibitors Of Metalloproteinasesmentioning
confidence: 93%
“…These vesicles stimulate capillary-like structure formation when added to endothelial cells seeded on a solubilized basement membrane preparation (Matrigel) [26].…”
Section: Extracellular Matrix Degradationmentioning
confidence: 99%